A Gap Exposed: What Is Known About Sikh Victims of Domestic Violence Abuse (DVA) and Their Mental Health? - Kaur-Aujla, Harjinder; Shain, Farzana; Lillie, A. Kate (European Journal of Mental Health, 2019)
There is emerging evidence that Domestic Violence and Abuse (DVA) has the potential to pose a real threat to the Sikh community as it seeks to ensure that gender equality is embraced within its religious practice. Nevertheless, the interface of domestic abuse and the distress it causes to Sikh female victims in relation to their mental health is barely explored within UK academic literature. From the existing literature on DVA and South Asian women, what we do know is that there may be a denial of the issue within communities due to shame and family exposure. We are aware of the high rates of suicide and self-harm that is prevalent within the South Asian culture, something often attributed to inter-familiar conflict. The pioneering community-led British Sikh Report or BSR (British Sikh Report 2017) surveyed 2000 Sikhs and found that seventy-two percent of Sikh-identifying males and females considered that violence and sexism affected British Sikh women’s lives. Notably, the type of violence was not particularised enough to be able to gain a full understanding and extent of the issue. A further eighty-three percent of male and female participants felt that women should be provided mental health support in Gurdwaras (temples). This grassroot report has been presented to Parliament and was pioneered by local MP’s and is clearly topical in terms of study. To date, we are aware of no UK-based academic study that focuses on the experiences of Sikh victims of abuse. This paper aims to extrapolate key generic studies on domestic abuse in the South Asian culture, in order to help formulate an initial understanding of issues involving domestic violence and mental health as it impacts Sikh women in Britain. Further recommendations for research within this community are presented.